Connector sets and interconnect components to be used in optical fibre communication systems. Product specifications. Type LX.5-PC DUPLEX terminated on IEC 60793-2-50 category B1.1 and B1.3 singlemode fibre, with full zirconia ferrule category U Part 13-2, (30th April 2011) - British Standards Institution,
No abstract available